Structural magnetic resonance neuroimaging of the parietal lobe in primary open angle glaucoma / Dr Mohammad Hanafiah - Hanafiah, Mohammad (Research Management Institute, 2014)
There has been increasing number of evidence linking primary open angle glaucoma and Alzheimer’s disease (AD). Both diseases are chronic, neurodegenerative, and progressive in nature associated with irreversible neuronal cell loss. Aside from medial temporal atrophy, parietal lobe atrophy is observed in patients with AD, particularly early onset AD. This is often best seen on the interhemispheric surface of the parietal lobe by examining the posterior cingulate sulcal and parieto-occipital sulcal size. The objective of the study is to determine if the increase incidence of parietal lobe atrophy observed in AD patients using Koedam Visual Rating is also present among patients with POAG.